Human-Like Spatial Reasoning Formalisms - Walega, Przemyslaw (Proceedings of the AAAI Conference on Artificial Intelligence, 2017)
My work on the PhD thesis concerns human-like reasoning about relations between spatial objects and the way they change in time. In particular, my research is focused on logic-based reasoning systems that model human spatial reasoning methods and may enable better understanding of humans reasoning mechanisms in future. Importantly, such formalisms are also interested from the practical point of view – they have a number of potential applications, e.g., in robotics, architecture design, databases, among others.